PENDAMPINGAN KELENGKAPAN ORGANISASI DAN PENERAPAN PRINSIP SYARIAH PADA KOPERASI BAITUL MAL WATAMWIL (BMT) PUNGGUR INTI SEJAHTERA KECAMATAN PUNGGUR - Fitriani, Fitriani; Sutarni, Sutarni; Yuniarti, Evi; Fatih, Cholid; Sudiyo, Sudiyo; Berliana, Dayang (Jurnal Pengabdian Nasional, 2022)
Community services were carried out at the Punggur Inti Sejahtera BMT Cooperative located inSidomulyo Village, Punggur District, Central Lampung Regency. Based on the problems faced bypartners, the priority justifications agreed with partners for solutions are increasing knowledge aboutthe completeness of cooperative organizations (Statutes and bylaws, legal entities) and the practice ofapplying sharia principles to improve cooperative financial reporting skills. Provide security and peaceof mind through transactions in sharia for the management and cooperative members so that theincome received is lawful and good for the members and management. They are helping to increasethe business capacity of cooperative members through increasing managerial ability in businessservices by applying sharia principles. The expected targets of PKM activities are: 1) Increasedknowledge of the completeness of cooperative organization and sharia principles for cooperativemanagement and members, 2) Improved skills in the practice of drafting AD/ART and filing forcooperative legal entities, 3) Increased ability of sharia transaction administration for cooperative management and members cooperatives and 4) Increased skills in preparing financial reports forcooperative management. The target audience is 23 members and the management of thecooperative. The PKM method carried out includes several stages, namely counseling onorganizational completeness and the application of sharia principles to cooperatives, the practice ofdrafting AD/ART and the requirements for filing cooperative legal entities, the practice of applyingsharia principles to cooperative businesses, and training in the preparation of cooperative financialreports. Activity outputs are a) Draft statutes, bylaws, and requirements for filing a combined legalentity. b) Cooperative financial transaction contract form according to sharia, b) Financial transactionreport, profit and loss, and cooperative financial position.